Dynein is required for polarized dendritic transport and uniform microtubule orientation in axons. - Zheng, Y.; Wildonger, J.; Ye, B.; Zhang, Y.; Kita, A.; Younger, S.H.; Zimmerman, S.; Jan, L.Y.; Jan, Y.N. (Nature Cell Biology, 2008)
Axons and dendrites differ in both microtubule organization and in the organelles and proteins they contain. Here we show that the microtubule motor dynein has a crucial role in polarized transport and in controlling the orientation of axonal microtubules in Drosophila melanogaster dendritic arborization (da) neurons. Changes in organelle distribution within the dendritic arbors of dynein mutant neurons correlate with a proximal shift in dendritic branch position. Dynein is also necessary for the dendrite-specific localization of Golgi outposts and the ion channel Pickpocket. Axonal microtubules are normally oriented uniformly plus-end-distal; however, without dynein, axons contain both plus- and minus-end distal microtubules. These data suggest that dynein is required for the distinguishing properties of the axon and dendrites: without dynein, dendritic organelles and proteins enter the axon and the axonal microtubules are no longer uniform in polarity.